ROLE OF VILLAGE CONSULTATIVE BOARD (BPD) IN VILLAGE ADMINISTRATION OF JANGGOLAN VILLAGES (Study in Sub-District of Sumpiuh Banyumas Region) - kadar Pamuji; Abdul Aziz Nasihuddin; Riris Ardhanariswari; Supriyanto Supriyanto (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Janggolan village is a village with limited locally generated revenue. In Sumpiuh sub-district there are 14 villages, 3 of which are the village of Janggolan. Village Fund Provision Policy in Law Number 6 Year 2014 on Villages affect on the performance of village apparatus and the quality of village community participation, while the Village Consultative Board (BPD) is expected to be an institution capable of playing role in village development. The problem is how the role of BPD in the implementation of Village Governance in the Janggolan village. The research was conducted by applying qualitative method with action research strategy. The results show that the Village Funds assisted the physical village development and work scheme but did not change the people attitude. BPD makes use of rembug warga (deliberation), selapanan (a traditional ceremony to commemorate a 35-day-old baby), and village meetings to accommodate aspirations and control the village. Yet they do not solve the village problems. The role of BPD in Janggolan village more focused on the absorption of people's aspirations. The internal constraints are low quality of members of BPD while the external constraints that BPD has not effectively performed. Keywords : deliberation, governance, societal participation.